Diseño de un captador de polvo de filtración seca para la fábrica de ladrillo la capilla en Sogamoso Boyacá (2023)
In the manufacture of brick, it is necessary to operate an oven, which is essential for the firing of clays and to obtain the final product. As a negative aspect generated within the operation we have emissions which contain particulate matter (PM) which is emitted to the environment affecting the community in general.